Perbedaan Peningkatan Kemampuan Pemecahan Masalah Matematika dengan Pendekatan Contextual Teaching and Learning di Kelas X - Agus Junsion Naibaho (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
One of the changes in learning paradigm is the teacher centered learning centered student centered; the methodology which was originally more dominated by expository switches to participatory; and a more textual approach turns contextual. Reality seen in the field, students only memorize the concept and are less able to use the concept if it encounters real life problems related to the concept. The purpose of this research is to know the difference of improvement of problem solving problem of student mathematics with CTL approach on material of two linear equation system in class X SMA Negeri 1 Dolok Batu Nanggar. Population in this research is all student of class X SMA Negeri 1 Dolok Batu Nanggar T.A. 2017/2018, which consists of 10 parallel classes with an average number of students per class is 30 people. This study was conducted on two classes representing the population and has the same characteristics. Sampling and sample class determination in this study was taken randomly, using random sampling technique with the consideration that the characteristics of the class that the population is the same. Class X-10 as control class and X-3 class as experiment class. The test used to obtain data is a description form. The data in this study were analyzed by using inferential analysis statistical analysis. Inferential analysis of data is done by t-test. The results showed that there was an improvement in problem-solving ability with conventional approach with better contextual approach Keywords : Problem Solving Abilities, Contextual teaching and learning Approach.